Cutaneous Smooth Muscle Tumors: A Clinicopathological Study Focusing on the Under-Recognized Histological Features - Asuman KILITCI; Ömer Faruk ELMAS (Federation of Turkish Pathology Societies, 2020)
Objective: Cutaneous smooth muscle tumors represent a rare group of cutaneous lesions including piloleiomyoma, angioleiomyoma, genital leiomyoma, smooth muscle hamartoma, and leiomyosarcoma. In this study, we aimed to evaluate the clinical and pathological characteristics of CSMTs, focusing on the rare and unspecified histological features. Material and Method: The clinical, demographic and histological findings of the patients with CSMTs were reviewed and evaluated retrospectively. The histopathological sections were re-evaluated for all cases. Results: A total of 32 patients with CSMTs were enrolled. The majority were female (n=20). The most common tumor diagnosed was angioleiomyoma (n=19, 59.4%) followed by piloleiomyoma (n=8, 25%), smooth muscle hamartoma (n=2, 6.3%), leiomyosarcoma (n=2, 6.3%), and genital leiomyoma (n=1, 3%). Five lesions were painful and only 3 specimens were submitted with the preliminary diagnosis of a cutaneous smooth muscle tumor. Conclusion: There are very few studies investigating both clinical and histological characteristics of CSMTs in detail. Along with the classical histological clues, evaluation of the clinical findings and less-defined histological features may enhance the diagnostic accuracy. To the best of our knowledge, this study represents the first original study focusing on the clinical and pathological aspects of CSMTs in our country.